Meta-Power: Next-Generation Smart Grid - HUANG Chao; BU Siqi; CHEN Qiyu; LEE Hiu Hung (发电技术, 2022)
Metaverse is a new stage of digital revolution,which transforms the universe to highly interactive and hyper-spatiotemporal eco-system supported by multiple technologies. The application of metaverse in the power system can further improve the informatization and intellectualization of the system,becoming the next generation smart grid. This paper proposed a new concept of meta-power to represent the power system introducing the metaverse. Multiple technologies of the meta-power can enhance the flexibility,security,and intelligence of the power system operation. High interactivity of the meta-power can enable the convenient and immersed power system monitoring and maintenance. Hyper-spatiotemporal feature of the meta-power can tackle the spatial and temporal constraints of the power system operation,and facilitate the evaluation and deduction of future energy development strategies.